Situational Impulsive and Compulsive Online Purchase of Fashion Products in Generation Z - Ekawati, Ni Wayan; Giantari, I Gusti Ayu Ketut; Indrawati, Komang Rahayu; Tirtayani, I Gusti Ayu; Sihombing, Irene Hanna H. (Mercados y Negocios, 2025)
This study investigates the situational factors influencing impulsive and compulsive online purchases of fashion products among Generation Z. The findings indicate that financial management has a negative and significant effect on impulsive buying, meaning that better financial management reduces the likelihood of impulsive purchases. On the other hand, materialism and socioeconomic status have a positive and significant impact on impulsive buying, indicating that stronger materialistic traits and higher socioeconomic status are associated with increased unplanned purchasing behavior.